PENGARUH STRUKTUR KEPEMILIKAN DAN KINERJA KEUANGAN TERHADAP KEBIJAKAN DIVIDEN - Mona Kartika, Ni Putu Silva; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
800x600 This study was to determine the effect the structure of institutional ownership, managerial ownership structure and financial performance on dividend policy. The population in this study is a manufacturing company in Indonesia Stock Exchange that has the institutional ownership, managerial ownership, and dividends four years in a row during the observation period 2010-2013 as many as 15 companies were examined as a whole ( sample saturated ) using analytical techniques multiple linear regression and partial test . The results showed that the structure of institutional ownership a significant negative effect on dividend policy, while the ownership structure of managerial and financial performance significant positive effect on dividend policy. Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";}
Keywords: structure of institutional ownership, managerial ownership structure of financial performance , dividend policy